Integrating climate finance and disaster-triggered instruments for climate resilience: A systematic review - Axel Giovanni; Erika Kurniasari; Galuh Witantri; Vierda Dwi Aprilia; Retno Sugiharti (Universitas Ahmad Dahlan, 2025)
The growing severity of natural disasters due to more unpredictable climate change disrupts the economic system requiring new financial tools to handle the related risks. Climate finance has become essential for aiding disaster risk reduction and preparedness efforts. Nonetheless, obstacles like insufficient alignment of financial tools with resilience approaches, governance issues, and restricted community capabilities impede its efficacy. This study systematically examines the role of climate finance in funding disaster risk reduction and preparedness efforts and how financial instruments activated by disasters can enhance the effectiveness of these initiatives. This research utilizes a systematic literature review that adheres to the preferred reporting items for systematic reviews and meta-analysis framework, examining 27 peer-reviewed publications from Scopus and Web of Science. The analysis indicates that financial tools activated by disasters can lower financial losses by as much as 25% in climate risk situations. Essential results emphasize the significance of government policies in enhancing these tools, the involvement of private sector funding, and the necessity for region-specific risk evaluation frameworks. Gaps in execution remain, especially in developing nations, arising from funding shortages, a 90 trillion deficit for green infrastructure by 2025, and governance inefficiencies. The incorporation of climate funding and disaster-related tools greatly improves community resilience and the stability of financial systems. This study can inform policy formulation for integrating climate finance governance to promote the swift advancement of financial instrument innovation, enhance local resilience, guarantee inclusive, and sustainable funding.